Hydrogen production from hydrolysis of magnesium wastes reprocessed by mechanical milling under air - Rodríguez, María; Niro, Franco; Urretavizcaya, Guillermina; Bobet, Jean Louis; Castro, Facundo (Pergamon-Elsevier Science Ltd, 2022)
Fil: Rodríguez, María. Comisión Nacional de Energía Atómica. Centro Atómico Bariloche; Argentina. Universidad Nacional de Cuyo; Argentina